Effectiveness of interventions for the management of primary frozen shoulder. (2021) - Rex, S. S.; Kottam, L.; McDaid, C.; Brealey, S.; Dias, J.; Hewitt, C. E.; Keding, A.; Lamb, S. E.; Wright, K.; Rangan, A.
No abstract available